From Borrowing to Blending: Rethinking the Processes of Organizational Theory Building - Oswick, Cliff; Fleming, Peter; Hanlon, Gerard (Academy of Management Review, 2011)
Why are there not more original and radical theories in organization theory? To answer this question, we consider an overreliance on “theory borrowing” from other disciplines. We identify a dominant foreign to domestic to domesticated pattern of organization and management theory building and propose that the prevalent process of one-way borrowing from outside the discipline should be counterbalanced by a two-way analogical process of conceptual blending, which involves dissonant thinking, disanalogy, and counterfactual reasoning.